Towards a Decolonial Abolition Feminist Methodology: A Research Project Exploring Women’s Experiences of Strip Searching in Prison - Hutchison, Jessica (Intersectionalities)

(untitled) (Memorial University of Newfoundland, 2024)
Engaging in research with Indigenous and Black women as a white woman settler involves critical considerations related to white supremacy, settler colonialism, and misogynoir. This is particularly true when the participants have been imprisoned and the researcher has not. As such, this article describes my unique abolition feminist methodology rooted in a framework of relational accountability which centred experiences of Black and Indigenous women who have been strip searched in prison. It describes the specific steps I took to enact the ethics of relational accountability – reciprocity, respect, and responsibility – in each phase of the research. This includes an innovative method of meaning-making whereby I listened to the recorded conversations with women while I was on the land of a federal prison. This facilitated more wholistic and embodied meaning-making as I was able to hear and feel what the women were sharing while being in the presence of a federal prison. I also engage in abolition feminist praxis by critically reflecting on the ways in which power and practices of superiority showed up throughout the research process.